The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1099/jmm.0.044727-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Epstein–Barr virus BamHI-A rightward transcripts and their expression patterns in lytic and latent infections

Abstract: Epstein-Barr virus (EBV)BamHI-A rightward transcripts (BARTs; also designated complementary strand transcripts or CSTs) have been demonstrated to contain several splicing forms in EBV-infected cells. To date, however, little is known about the actual full-length splicing form and its functions. In the present study, we proved that six forms of BARTs were present in EBV-positive cell lines and various tissue specimens with different EBV infection patterns. Of the BART-encoded genes, mRNA of four major splicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…RNA was extracted from the samples with TRIzol ™ reagent (Gibco‐BRL, Gaithersburg, MD, U.S.A.), and the cDNA was amplified by PCR using EBER1‐specific and Bam HI A rightward transcripts (BARTs)‐specific primers, as described previously . The integrity of the RNA was checked by the parallel amplification of beta‐2‐microglobulin (β2‐MG).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from the samples with TRIzol ™ reagent (Gibco‐BRL, Gaithersburg, MD, U.S.A.), and the cDNA was amplified by PCR using EBER1‐specific and Bam HI A rightward transcripts (BARTs)‐specific primers, as described previously . The integrity of the RNA was checked by the parallel amplification of beta‐2‐microglobulin (β2‐MG).…”
Section: Methodsmentioning
confidence: 99%
“…Primer sets for reverse-transcriptase polymerase chain reaction RNA was extracted from the samples with TRIzol TM reagent (Gibco-BRL, Gaithersburg, MD, U.S.A.), and the cDNA was amplified by PCR using EBER1-specific and BamHI A rightward transcripts (BARTs)-specific primers, as described previously. 11,12 The integrity of the RNA was checked by the parallel amplification of beta-2-microglobulin (b2-MG). To detect EBV reactivation, BZLF1 was amplified by RT-PCR, using BZLF1-specific outer primers: sense, 5ʹ-CATGTTTCAACCGC TCCGACTGG-3ʹ, and antisense, 5ʹ-GCGCAGCCTGTCATTTTCA GATG-3ʹ.…”
Section: Patientsmentioning
confidence: 99%
“…Eight of these EBV transcripts ( BARF0 , BALF3 , BALF4 , BALF5 , A73 , RPMS1 , LF2 and LF1 ) are encoded in the Bam H1A region of the viral genome where the expressed viral miRs are also encoded. 10 , 65 , 85 Although the medical literature suggests that latent membrane protein 1 is infrequently expressed in infected gastric adenocarcinoma by protein assays, TCGA RNAseq revealed that both EBV latent membrane protein encoding mRNAs ( LMP1 , LMP2A ) were consistently expressed, albeit at low level. Latent membrane protein 2 or other viral gene products may contribute to hypermethylated DNA that is characteristic of infected cancers.…”
Section: Ebv Gene Expressionmentioning
confidence: 99%
“…However, there is still a lack of supporting evidence for the expression of endogenous BART proteins in EBV-infected cells ( 44 , 79 ). It is also surprising to note that the expression levels of BART are known to vary depending on whether the infection is lytic or latent ( 45 ). These findings demand further detailed investigation to elucidate the potential roles of the BART proteins in the pathogenesis of EBV-induced NPC.…”
Section: Ebv Protein Expressionmentioning
confidence: 99%